Monetary Policy and Fiscal Policy: Impact Effects with a New Keynesian 'Assignment' of Weapons to Targets. - Meade, J; Vines, D (CEPR, 1988)
This paper considers fiscal and monetary policy in a short-run static macroeconomic model. There are two objectives, control of inflation and control over the growth of national wealth, and a third outcome of importance, a high level of employment. There are two instruments, monetary policy (the short-term interest rate) and fiscal policy (the rate of income tax). The assignment problem considers whether fiscal policy should be used to control inflation, leaving monetary policy to affect the accumulation of wealth, or whether these roles should be reversed. We consider 'pure' and 'mixed' assignments. The analysis shows that the appropriate assignment will depend fundamentally on the relative strengths of demand-pull and cost-push factors in the determination of wages.